The Proteome and Lipidome of Thermococcus kodakarensis across the Stationary Phase. (4th May 2016) - Gagen, Emma J.; Yoshinaga, Marcos Y.; Garcia Prado, Franka; Hinrichs, Kai-Uwe; Thomm, Michael
Abstract : The majority of cells in nature probably exist in a stationary-phase-like state, due to nutrient limitation in most environments. Studies on bacteria and yeast reveal morphological and physiological changes throughout the stationary phase, which lead to an increased ability to survive prolonged nutrient limitation. However, there is little information on archaeal stationary phase responses. We investigated protein- and lipid-level changes in Thermococcus kodakarensis with extended time in the stationary phase. Adaptations to time in stationary phase included increased proportion of membrane lipids with a tetraether backbone, synthesis of proteins that ensure translational fidelity, specific regulation of ABC transporters (upregulation of some, downregulation of others), and upregulation of proteins involved in coenzyme production. Given that the biological mechanism of tetraether synthesis is unknown, we also considered whether any of the protein-level changes in T. kodakarensis might shed light on the production of tetraether lipids across the same period. A putative carbon-nitrogen hydrolase, a TldE (a protease in Escherichia coli ) homologue, and a membrane bound hydrogenase complex subunit were candidates for possible involvement in tetraether-related reactions, while upregulation of adenosylcobalamin synthesis proteins might lend support to a possible radical mechanism as a trigger for tetraether synthesis.